AN ANALYTICAL STUDY OF PRESENT POSITION OF BITCOINS - Mittal, Alka (International Journal of Research -GRANTHAALAYAH, 2017)
Bitcoin is a virtual currency that is created from computer code. It has no central bank and is not backed by any government. But it can be exchanged for goods and services or for any other currencies. They were launched in 2009 as a bit of software written under the name Satoshi Nakamoto. The present paper analyse the Indian Tax and legal considerations regarding Bit coins. It also analyse the problems and risks related with Bitcoins.